The treatment of chronic wounds using bacteriophages - Katarzyna Bil; Justyna Kiełbasa; Agata Kowalczyk; Natalia Zozula; Aleksandra Latała; Iga Ślesicka; Aleksandra Rykucka; Marcin Wąs; Magda Przestrzelska; Zuzanna Tomczewska (Kazimierz Wielki University, 2024)
Introduction and aim of study: Chronic wounds are increasingly challenging global healthcare. These wounds, which take over 3 months to heal, are complicated by untreated infections and the formation of biofilm, hindering healing and antibiotic effectiveness. To tackle these issues, new treatments like bacteriophage therapy are being explored. Bacteriophages, viruses that target bacteria, offer promise in overcoming antibiotic resistance. However, their use presents challenges that need to be addressed. Material and methods:  Our review is based on the analysis of materials collected in Pubmed, Elsevier and other scientific articles using keywords: "chronic wound", "chronic wounds infection", "biofilms", "MDR", "bacteriophage", "phage therapy". Conclusions: The rise of chronic wounds due to resistant infections poses a significant challenge for patients and healthcare systems. Multidrug-resistant bacteria, often forming biofilm, evade current treatments, urging the search for alternatives. Phage therapy, showing efficacy against various stubborn infections, including those from surgery or diabetes, gains attention. Advanced delivery systems enhance targeted treatment, while phage cocktails improve effectiveness, especially against multiple resistant strains. Safety is generally observed, but larger trials are needed. Though not a replacement for antibiotics, phage therapy offers hope, needing robust clinical validation. While challenges exist, its societal, commercial, and economic benefits suggest a promising future beyond clinical use.